1986
DOI: 10.1111/j.1365-2125.1986.tb02875.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo cation transport during short‐term and long‐term digoxin therapy.

Abstract: We have studied the effects of digoxin on cation transport in vivo by measuring the changes in plasma and red cell rubidium concentrations following an oral load of rubidium chloride. In eight patients who had been taking digoxin for 7 to 10 days (mean plasma digoxin concentration 1.3 ng ml‐1) the rise in plasma rubidium concentrations was enhanced and the rise in red cell rubidium concentrations was attenuated following the oral load of rubidium chloride, by comparison with the changes in well‐matched control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Another possible explanation is that ouabain was rapidly cleared by ciliary clearance mechanisms, but if this were the case amiloride would likewise have been ineffective. Inadequate drug penetration is unlikely to explain the lack of effect of oral digoxin, however, as a similar plasma concentration to those obtained in this study has previously been shown to cause widespread inhibition of tissue Na+-K+-ATPase in healthy subjects [31] after a similar length of treatment. Although a small rise in nasal P D was seen after the first week of digoxin, the increase was not statistically significant and was absent by the second week.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Another possible explanation is that ouabain was rapidly cleared by ciliary clearance mechanisms, but if this were the case amiloride would likewise have been ineffective. Inadequate drug penetration is unlikely to explain the lack of effect of oral digoxin, however, as a similar plasma concentration to those obtained in this study has previously been shown to cause widespread inhibition of tissue Na+-K+-ATPase in healthy subjects [31] after a similar length of treatment. Although a small rise in nasal P D was seen after the first week of digoxin, the increase was not statistically significant and was absent by the second week.…”
Section: Discussionsupporting
confidence: 77%
“…Oral digoxin has a peak cardiac effect at 5h, with a half-life of 36h [22]. After short-term administration (over days to weeks), digoxin produces widespread inhibition of cardiac Na+-K+-ATPase, although after several months this effect may be lost due to pump upregulation [31]. The effect of digoxin on nasal PD was investigated over 2weeks to avoid this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to overcome the difficulties associated with measures in vitro, we have developed a technique which allows the assessment of cation transport in vivo [ 171. This has already been used to demonstrate differences in sodium pump activity in patients suffering from hypertension [18] and chronic renal failure [17] and during treatment with digoxin [17,19]. We have now used this technique in vivo to assess the effect of treatment with lithium salts upon cation transport in healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%